PENGARUH MOTIVASI BELANJA, CITRA DESTINASI, DAN PENGALAMAN TERHADAP NIAT BERKUNJUNG KEMBALI KE PUSAT PEMBELANJAAN - Rahayu Mardikaningsih; Ana Arifiana; Firza Fahriza; Novita Faramedina; Ersa Dina (Sekolah TInggi Ilmu Administrasi dan Manajemen Kepelabuhan (STIAMAK) Barunawati Surabaya, 2023)
The current research intends to determine the influence of shopping motivation, destination image, and experience on revisit intentions. In this study, the population is shopping center visitors who have returned to Cito Surabaya. The sample is known as 100 respondents. Samples were taken using purposive sampling technique. The Google form is the application used to collect research data from this study through a questionnaire. Processing the data according to the collected will utilize SPSS to analyze the results. In accordance with the objectives identified, it resulted in findings that of the three independent variables, namely shopping motivation, destination image and experience can significantly influence the revisit intention. This research can assist shopping center managers in understanding consumers and designing marketing strategies that suit their needs.